PENGARUH METODE LEARNING START WITH A QUESTION (LSQ) TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI EKOSISTEM - Rizka Robiatul Addawiyah; Idad Suhada; Muhammad Muttaqien (Jurnal BIOEDUIN : Program Studi Pendidikan Biologi, 2015)
The study was conducted in class VII-Purwakarta MTsN Plered on ecosystems material. Based on direct observation and interviews with teachers in MTs.N Plered that the activity of the class students are less active, critical thinking skills of students in the lower grade and variation model of applied learning teacher less. So that students actively in class and increase students' critical thinking skills used method Start Learning With A Question in the learning process. This study aims to determine the enforceability of the learning process by applying learning methods start with a question. Increasing students' critical thinking skills, and student responses to learning using learning methods start with a question on the material ecosystem. The framework of this research that students are required to actively ask especially at the beginning of the learning process of the student asks a thought process that is carried out in order to solve the problems of students in learning. This learning process with such students will be active in class and critical thinking would be formed. Method Start Learning With A Question is an active learning method in asking, where students are directly involved in the learning process. Active asked at the beginning of the learning will stimulate students to think critically about the material to be conveyed. From the data processing gained an average of N-Gain increase students' critical thinking skills in the experimental class 0.54 and the control class 0.49. To look significantly on the ability of critical thinking among students learning with Learning methods Start With A Question and without using the Start Learning With A Question presented through pretest and posttest values as well as the N-Gain. To prove this hypothesis significance test was used to test t nomalitas first tested and homogeneity. Because one of the data is not normal, the Mann-Whitney test. Based on the results of Mann-Whitney test scores N-Gain between the experimental class and the control class result that Zhitung> Ztabel. thus Zhitung> Ztabel ie 1.98> 1.65; Ho is rejected and Ha accepted meaning there is influence between the N-Gain pretest and posttest experimental class with N-Gain pretest and posttest control class. It can be concluded that there are significant learning method Start With A Question to increase students' critical thinking skills in ecosystem material.